Inert shell effect on the quantum yield of neodymium-doped near-Infrared nanoparticles: the necessary shield in an aqueous dispersion - Skripka, Artiom (2021)
Lanthanide-doped nanoparticles (LnNPs) are versatile near-infrared (NIR) emitting nanoprobes that have led to their growing interest for use in biomedicine-related imaging. Toward the brightest LnNPs, high photoluminescence quantum yield (PLQY) values are attained by implementing core/shell engineering, particularly with an optically inert shell. In this work, a thorough investigation is performed to quantify how an outer inert shell maintains the PLQY of Nd3+-doped LnNPs dispersed in an aqueous environment. Three relevant quantitative findings affecting the PLQY of Nd3+-doped LnNPs are identified: (i) the PLQY of core LnNPs is improved 3-fold upon inert shell coating; (ii) PLQY decreases with increasing Nd3+ doping despite the inert shell; and (iii) solvent quenching has a major influence on the PLQY of the LnNPs, though it is relatively lessened for high Nd3+ doping. Overall, we shed new light on the impact of the LnNP architecture on the NIR emission, as well as on the quenching effects caused by doping concentration and solvent molecules.